(untitled) (Journal of Pakistan Orthopaedic Association, 2021)
Objective: To determine the effectiveness of intra-articular injections of Platelet Rich Plasma (PRP) in early Osteoarthritis knee in terms of pain reduction and improvements in functional outcome. Methods: This descriptive study was conducted in Department of Orthopedics Surgery Punjab Rangers Teaching Hospital Lahore/ Rahbar Medical and Dental College Lahore from 23rd March 2018 to 23rd March 2021.All patients with early osteoarthritis knee fulfilling the inclusion criteria were administered two intra-articular pure PRP injections. Follow up assessment was done at 6 weeks, 3 months, 6 months and one year for pain reduction measured on Visual Analog Scale (VAS) and functional improvement assessed with Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) questionnaire. The pre and post injection WOMAC and VAS values were compared P value calculated with Student-t test. P value <0.05 was considered significant. Results: Two intra-articular injections of PRP were administered to 84 knees in 61 patients. Female patients were 35(57.37%) and male 26(42.62%). The mean age was 61.5±2.3 years. Majority (60.71%,n=51) of knees had grade II Osteoarthritis while 33(39.28%) knees had grade I Osteoarthritis. In each follow up visit a significant improvement (P <0.05) in pain reduction(VAS) and functional outcome(WOMAC) was observed which persisted till last follow up visit at one year follow up. No complication was reported. Conclusion: Two intra-articular PRP injections in early Osteoarthris knee yielded significant reduction in pain and improvement in functional outcome.